A STUDY ON SCOPE, IMPORTANCE AND GROWING IMPORTANCE OF GREEN ACCOUNTING IN INDIA - Dr. Minti Sinha (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Green Accounting has gain the popularity over the period of time. It measures environmental and natural resources accounting. It attempts to bring in the environmental costs of the firm into the financial statement of the organisations. Its focused on the resource management and impact on the environment. It helps the organisations to identify the resources utilization and incurred costs. Green Accounting is in the developing stage at the corporate and at the national level. The objective of this study is to understand the scope , importance and to analyse the growing importance of Green Accounting in India. Secondary data are used for the study. Which are collected from published journals, Articles and website. Descriptive Research Design is used for the study. During the study it is found that the scope of the Green accounting is wider from the internal and external perspective. It has a number of importance. And the importance of Green Accounting is growing rapidly in India.